The use of tranexamic acid for post-tonsillectomy hemorrhage: A scoping review protocol - Naomi Tesema; Sukaina Hasnie; Marisa Earley; Max April (PLoS ONE, 2025)
Background Post-tonsillectomy hemorrhage (PTH) is a highly studied outcome of tonsillectomy with serious consequences. Various treatments and interventions have been utilized to decrease post-tonsillectomy hemorrhage. The off-label use of tranexamic acid (TXA) is of growing interest to control PTH but has not been incorporated in management guidelines. This scoping review plans to summarize existing studies from the scientific literature on the use of tranexamic acid for post-tonsillectomy hemorrhage. Methods We used the Preferred Reporting Items for Systematic Reviews or Meta-Analysis Extension for Scoping Reviews (PRISMA-ScR). The review will cover studies including patients undergoing tonsillectomy who were treated with TXA in the peri—operative or post-operative period. We include randomized controlled trials, retrospective, prospective, and case series. A database-specific search strategy will be used to search records across. Two reviewers will independently screen and extract data. Tables and visual representations will be utilized to present the extracted data. Registration details The protocol will be registered in Open Science Framework and published in PLOS One.